1971
DOI: 10.4141/cjas71-082
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Physiological Implications of Saponins: A Review

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
4

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 2 publications
(3 reference statements)
5
76
1
4
Order By: Relevance
“…22 The Saponin paradox is explained by the fact that hemolytic saponins are toxic when given via intravenous route. 23,24 This study observed increase in mean platelet volume in the 75 mg/kg aqueous extracts showing improved platelet quality, hence its possible role in hemostatic as earlier reported. 10 Increased mean platelet volume is an indication of larger and more reactive platelets resulting in increased platelet turnover.…”
Section: Discussionsupporting
confidence: 57%
“…22 The Saponin paradox is explained by the fact that hemolytic saponins are toxic when given via intravenous route. 23,24 This study observed increase in mean platelet volume in the 75 mg/kg aqueous extracts showing improved platelet quality, hence its possible role in hemostatic as earlier reported. 10 Increased mean platelet volume is an indication of larger and more reactive platelets resulting in increased platelet turnover.…”
Section: Discussionsupporting
confidence: 57%
“…The soyasaponins are mainly present in legumes, and significant amounts of soyasaponins are found in soybeans and soy products (John et al, 2004). The potential relationship of soyasaponins to health effects has been suggested (Cheeke, 1976;Potter et al, 1979;Messina et al, 1994;Messina, 1995;Joel and Zhang, 2008). Indeed, soyasaponins have anti-carcinogenic, hepatoprotective and antiviral activities, and soyasapogenol N exhibits antigenotoxic, hepatoprotective, and cytotoxic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon the results from the current study we tentatively conclude that of these factors, microbial digestion was the most important. Although our digestibility measurements cannot be used to differentiate degradability in the digestive tract from absorption, other data suggest that insignificant amounts of saponins cross the gut and enter the blood stream (Cheeke 1971;Small et al 1990). In contrast, although we are unaware of any studies in which the apparent digestibility of alfalfa saponins has been measured, it is known that rumen bacteria can degrade saponins (Gutierrez et al 1958;Gutierrez and Davis 1962).…”
Section: Degradability Of Saponins In the Digestive Tractmentioning
confidence: 77%